Two anisakid nematodes from marine fishes off New Caledonia, including Raphidascaris (Ichthyascaris) nemipteri n. sp. from Nemipterus furcosus - Moravec, Frantisek; Justine, Jean-Lou (Systematic parasitology, 2005)
One new and one known species of the ascaridoid family Anisakidae are reported from marine fishes off the southwestern coast of New Caledonia: Raphidascaris (Ichthyascaris) nemipteri n. sp. from the intestine of the forked-tailed threadfin bream Nemipterus furcosus (Nemipteridae, Perciformes) and Hysterothylacium cenaticum (Bruce and Cannon, 1989) from the intestine of the striped marlin Tetrapturus audax (Istiophoridae, Perciformes). R. nemipteri is characterised mainly by the shape (wider than long) of the lips, the length of the spicules (225-399 microm, which represent 2.7-4.2% of the body length), the number (22-33) of caudal pre-anal papillae, the position of the vulva (at 16-20% of the body length), and the presence of cuticular spines on the tip of the female tail. Specimens of H. cenaticum from New Caledonia generally exhibited smaller body measurements than those originally described from Australian waters; the deirids and eggs are described for the first time. Maricostula Bruce and Cannon, 1989 is considered a junior synonym of Hysterothylacium, to which three species are transferred as H. cenaticum (Bruce and Cannon, 1989) n. comb., H. makairi (Bruce and Cannon, 1989) n. comb. and H. tetrapteri (Bruce and Cannon, 1989) n. comb.
Keywords: mořská voda; Nová Kaledonie; Perciformes; střeva; Ascaridoidea; Animals; Intestines; New Caledonia; Female; Seawater; ženské pohlaví; mikroskopie elektronová rastrovací; Microscopy, Electron, Scanning; zvířata